A survey on English linguistic ability of the government primary school children prior to introduction of Interactive Radio Instruction (IRI) Programme - Khan, Kaisar A. (BRAC Research and Evaluation Division (RED), 2019)
With the a£.f Directorate of Primary Education (DEP) of the government of Bangladesh, BRAC is introducing the Interactive Radio Instruction (IRI) programme on a pilot basis in 17 government primary schools. The primary objective of the programme is to teach English to the learners of grade two. This study aimed at assessing the basic level of English linguistic ability of the learners before the programme starts. It investigated the gender difference (if any) of the level of knowledge in basic English and examined relationship between such knowledge and parental socioeconomic background. ~ purpose, 320 learners ( 160 boys and 160 girls) were tested through a set of questionnaire and tools developed following the curriculum oft he IRI course. The learners scored 29.5 on average, out of 102. The boys scored insignificantly higher (30.3) than the girls (28.7). The study also found that the learners from rich families performed better in the test . IV indicates that aggregate educational level of families, occupation of parents, ages of the learners, and reputation of schools were the influential determinants not only for learning English but also in acquiring knowledge on other subjects .